Study on the effect of flux composition on the melting efficiency of A-TIG of AISI 316L stainless steel: Experimental and analytical approaches - Peyman Binande; Hamid Reza Shahverdi; Amirreza Farnia (Journal of Materials Research and Technology)
Melting efficiency in welding is determined by various factors, including processing and operational parameters, the thermomechanical and chemical properties of the materials, surface conditions, and the type of energy source. This study uses a dimensionless parameter approach to evaluate melting efficiency by estimating the weld pool area through experimental measurements of the weld bead's diameter and depth. Also, this study investigates surface-active oxide fluxes based on SiO2 with Cr2O3 and Fe2O3 additives in TIG welding of 316L stainless steel. The effects of these fluxes on melting efficiency, weld cross-sectional area, microstructure, and mechanical properties at various currents (100–200A) were evaluated using metallographic, mechanical, and chemical analyses. The results show that using two-component fluxes at steady incident energy increased melting efficiency in the experimental approach by approximately 10% compared to single-component fluxes and by 20% compared to the without flux condition, providing more favorable and realistic outcomes than the analytical approach. This increase in melting efficiency resulted in a rise in the δ-ferrite phase (7.6% volume) and a reduction in the oxygen content (256 ± 10 ppm) in the weld metal. Furthermore, the two-component fluxes caused arc column constriction, which enhanced absorbed energy and led to an equiaxed grain microstructure with increased penetration depth. The weld metal's strength (630 ± 4 MPa) was directly linked to the penetration depth. However, the high absorbed energy caused grain growth, decreasing weld metal hardness (202 ± 2.5 HV) as melting efficiency increased.